Mitochondrial genomes of the South American electric knifefishes Eigenmannia humboldtii (Steindachner 1878), Eigenmannia limbata (Schreiner and Miranda Ribeiro 1903), Sternopygus aequilabiatus (Humboldt 1805) and Sternopygus macrurus (Bloch and Schneider 1801), (Gymnotiformes, Sternopygidae). Issue 2 (3rd July 2018) - Rincón-Sandoval, Melissa; Betancur-R, Ricardo; Maldonado-Ocampo, Javier A.
Abstract: We report four mitochondrial genomes of South American electric knifefishes, derived from target capture and Illumina sequencing (HiSeq 2500 PE100). Two trans-Andean species Eigenmannia humboldtii (mitochondrial consensus genome of 25 individuals) and Sternopygus aequilabiatus (mitochondrial consensus genome of 30 individuals) from Colombia and two cis-Andean species Eigenmannia limbata from Suriname and Sternopygus macrurus from Argentina. Regarding Eigenmannia humboldtii, Eigenmannia limbata, and Sternopygus macrurus mitochondrial genomes have 13 protein-coding genes, 1 D-loop, 2 ribosomal RNAs, 22 transfer RNAs, and are 13, 394 bp, 10, 921 bp, and 13, 013 bp in length respectively, for Sternopygus aequilabiatus mitochondrial genomes have 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and is 14, 270 bp in length.